A new genus and new species of Meropathina from Lord Howe Island (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2018)
Prototympanogaster new genus and P. lordhowensis new species (Hydraenidae: Ochthebiinae: Meropathina), are described based on two male specimens collected on Mount Lidgbird, Lord Howe Island, Australia. The new genus is related to the Australian genus Tympanogaster Perkins 1979, but lacks the diagnostic metaventral tabella of members of that genus. High resolution images of the holotype, illustrations of the male genitalia, and photographs of the habitat are provided. Relationships to the other genera now known for the subtribe Meropathina (Ochthebiinae, Ochthebiini) are discussed, habitus images and diagnostic features of representative species are presented, and a key to the genera of Meropathina is provided.